Nonlinear Vibration Feature Recognition Method for Reciprocating Compressor Cylinder Based on VMD-Multifractal Spectrum - Fengxia Lyu; Caiqian Xie; Fengfeng Bie; Xinting Miao; Yifan Wu; Ying Zhang (Shock and Vibration)
The failure probability of piston ring abrasion occupies the forefront in reciprocating compressor cylinder assembly. Due to the reciprocating friction between the piston ring and cylinder liner, the local vibration signal contains typical nonstationary characteristics with a seriously overlapped frequency band of impact signals, while the different featured signals are coupled with each other. Therefore, the identification of cylinder friction and abrasion fault modes has always been a hot and difficult problem in fault diagnosis of reciprocating compressors. In order to monitor the friction and abrasion between low linear speed nonmetallic piston ring and cylinder liner of reciprocating compressor in refinery and provide a theoretical basis for preventive maintenance, an analysis method based on VMD-multifractal spectrum was presented in this paper. First, the feasibility of the proposed method was proven based on the cylinder vibration experiment of a reciprocating compressor in the laboratory. Then, an in-service reciprocating compressor in a refinery was taken as the research object, from which the cylinder friction vibration signals were processed by using variational mode decomposition to obtain a band-limited intrinsic mode function (BLIMF). Multifractal detrended fluctuation analysis is employed in the final abrasion pattern identification. The results show that the proposed method based on VMD-multifractal spectrum analysis can effectively obtain the abrasion state of a piston ring, which can avoid blind overhaul or provide the basis for preventive maintenance and a practicable engineering route for the study of the piston ring abrasion degree.